Detection of added plastics in the frying oils using differential scanning calorimetry (DSC) combined with principal component analysis (PCA) - M.S, Mualim; Tukiran, Nur Azira; Abdullah Sani, Muhamad Shirwan; Fadzillah, Nurrulhidayah (Politeknik Nilai Negeri Sembilan (PNS), 2018)
There was a controversy on the claimed usage of plastic bags and straws which were intentionally added in the frying oil just to make fried foods crunchier. Thus, the present study was aimed to assess the feasibility of Differential Scanning Calorimetry (DSC) coupled with Principal Component Analysis (PCA) in detecting the added plastics in the frying oils. The method used was able to detect the added plastics in the frying oils that have been used to fry banana, onion and chicken. The simple approach employing DSC and PCA reported in this study may provide a useful tool for food safety.